PENDIDIKAN POLITIK PEREMPUAN DALAM KONTEKS NEGARA DEMOKRASI - Bambang Rudi Harnoko (UIN K.H. Abdurrahman Wahid Pekalongan, 2012)
Abstract : The de jure government has given full support in improving the quality and quantity of women's political, affirmative strategy of 30% quota for women. However, this strategy can not guarantee women's role in politics optimally. Therefore, sanggatlah important to make efforts to improve the quality and quantity of the representation of women's representation in politics. Especially in the context of democracy, which should give the right to the same opportunities to all the people, both men and women in voicing their aspirations as a manifestation of their political rights. Untuuk realize it all, required education as a vehicle for increasing women's political empowerment and the ability to actualize their role as citizens. Abstrak :Â SecaraÂ de yure,Â Pemerintah telah memberikan dukungan penuh dalam meningkatkan kualitas dan kuantitas politik, strategi afirmatif perempuan kuota 30% bagi perempuan. Namun, strategi ini tidak dapat menjamin peran perempuan dalam politik secara optimal. Oleh karena itu, sanggatlah penting untuk membuat upaya meningkatkan kualitas dan kuantitas representasi keterwakilan perempuan dalam politik. Terutama dalam konteks demokrasi, yang harus memberikan hak untuk kesempatan yang sama untuk semua orang, baik laki-laki dan perempuan dalam menyuarakan aspirasi mereka sebagai manifestasi dari hak-hak politik mereka. Untuuk mewujudkan itu semua, diperlukan pendidikan sebagai wahana untuk meningkatkan pemberdayaan politik perempuan dan kemampuan untuk mengaktualisasikan peran mereka sebagai warga negara